Status Hematologi, Kadar IgG dan IgA Tikus yang Mengonsumsi berbagai Variasi Jumlah Tempe Kedelai Hitam - Nurrahman Nurrahman; Mariyam Mariyam (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Consumption of black soybean tempe can provide rapid improvement in children with poor nutritional status and/or suffering from diarrhea. The antioxidant activity of black soybean tempe is higher than yellow soybean tempe. This study aimed to examine the effect of the amount of black soybean tempe in the feed on hematological status, IgG levels, and IgA levels of rat blood. There was a total of 6 groups, each containing 5 rats. The rats were kept in animal laboratories at room temperature (25–27°C) for 25 days. The six groups were induced Enteropathogenic Escherichia coli (EPEC) suspension with a concentration of 107 CFU / mL of 1 mL per day for seven days, orally using a feeding tube. Parameters analyzed included hematology status, IgG levels and IgA levels. The administration of black soybean tempe had an effect on increasing hemoglobin levels, the number of erythrocytes and the percentage of hematocrit, and it gave the effect of decreasing the number of leukocytes and platelets of rat blood induced with EPEC bacteria. The group of rats that consumed black soybean tempe had no influence on IgG and IgA levels of blood plasma.